PELATIHAN TEKNIK 4D: PENGEMBANGAN KOMPETENSI KONSELOR TEMAN SEBAYA DALAM MENGIDENTIFIKASI PERILAKU TIDAK NORMAL - Arianti, Endah Fajri; Musslifah, Anniez Rachmawati; Zulkarnain, Zulkarnain; Kusuma, Afiifah Ramadhani (Gapenas Publisher, 2025)
Abnormal behavior in adolescents can negatively impact their psychological and social development. Therefore, the active role of peer counselors is needed in identifying and providing appropriate support. This community service activity aims to improve the competence of peer counselors through 4D (Define, Design, Develop, Disseminate) technique training. The training method involves an interactive approach in the form of discussions, case simulations, and skill evaluations of participants. The results of the activity showed an increase in the understanding and skills of peer counselors in recognizing and handling abnormal behavior in their environment. Thus, this training is expected to contribute to the creation of a more supportive environment for adolescents in dealing with their psychological and social problems